A Meta-Analysis of Studies on Groupware for Collaborative Work Environments - Birgul Kutlu; Yeliz Gunal Aggul; Idil Atasu; Zeynep Kaymaz (Proceedings, 2021)
This meta-analysis examines the studies on groupware published between the years 2010 and 2020. Descriptive analysis was conducted to determine the distribution of studies in terms of publication year, time–space matrix category, targeted sectors, research methods, and the academic field of the journals that published these studies. Although groupware played a significant role in communication, collaboration, and coordination of users in various collaborative work conditions and sectors, the majority of studies focused on asynchronous and distributed collaborative work environments in the software engineering field, and the research method preferred was design science.